El método viso-audio-motor-gnósico: un proceso didáctico para superar la disortografía - Carrión Celi, Nayely Yimabel (2024)
The Curricular Integration Work entitled 'The visuo-audio-motor-gnostic method: A didactic process to overcome dysorthography' aims to identify the main factors influencing dysorthography in students' learning processes. The goal is to enhance spelling skills through methodological strategies, such as the visuo-audio-motor-gnostic method, enabling students to learn and apply grammatical rules accurately. This research is descriptive in nature, with a mixed approach and quasi-experimental design. The theoretical framework addressed selected topics related to the visuo-audio-motor-gnostic method and dysorthography. Throughout the investigative process, scientific, analytical, synthetic, descriptive, and statistical methods were employed; data collection involved interviewing the teacher, and an initial assessment was administered to the students to diagnose spelling skill development. The study population comprised one teacher and nineteen fourth-grade students from the "A" class of the Basic Education School "Dra. Matilde Hidalgo de Procel." Initial results reveal the need for improvement actions, as a significant percentage of students reach the stable or secure level, while a considerable percentage attain the insecure level, indicating difficulties in mastering punctuation marks, orthographic accentuation, the use of capital letters, ambiguous letters, and, in general, a need to enhance mastery of spelling rules. To address this issue, the proposal 'multisensory spelling learning: awaken your senses to overcome dysorthography' was planned and executed. Its effectiveness was confirmed with the second application, during which the data, presented in a comparative table, demonstrated significant changes. Thus, it is concluded that the visuo-audio-motor-gnostic method constitutes an innovative and effective didactic process for developing spelling skills and overcoming dysorthography.